Restructuring of the Membership and Mandate of the Research, Extension Farmers Linkage Committees - Dalaa, Mustapha Alasan; Forkuor, Gerald; Ruber, Stella; Yeboah, Stephen; Siameh, Paul; Anku, Prospera; Kyere, Reginald (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
AICCRA Ghana in collaboration with USAID PolicyLink and the Ministry of Food and Agriculture (MoFA) and AICCRA Ghana led by the International Institute of Tropical Agriculture (IITA) organized an in-person stakeholders meeting on June 7, 2023. to discuss the merits and demerits of Research-Extension-Farmer Linkage Committee (RELCs) proposal to expand the membership of the RELCS to include Ghana Meteorological Agency and private Climate Information Services producers. The meeting was attended by stakeholders from Ghana Meteorological Agency, Private CIS providers, representatives from academic institutions and NARs, and members of the National Coordinating Committee, RELCs.